Consideraciones Sobre la Importancia de la Implementación de la Computación GRID en el Entorno Universitario Colombiano - Rodríguez Jiménez, Carlos Eduardo; Pérez Castillo, José Nelsón (Ingeniería, 2004)
The grid computing technology with origins at the great universities and research institutions of the world, enable potential of computing, transferring and storing information at higher scale over resources distributed on local networks and Internet, giving significant opportunities for the development of interinstitutional cooperation projects with diversity of applications and services. This work sketches the actual state of the technology components of grid computing and examines its level of utilization at the colombian higher education, with the purpose to verify the importance of introduce, not only the features of innovation that a university could offer at this field, without, the result of its productive implementation for the enforcement of their own academic projects, research and interaction with the society and private sector.